2015
DOI: 10.1017/s0952523814000364
|View full text |Cite
|
Sign up to set email alerts
|

CaV3.2 KO mice have altered retinal waves but normal direction selectivity

Abstract: Early in development, before the onset of vision, the retina establishes direction-selective responses. During this time period, the retina spontaneously generates bursts of action potentials that propagate across its extent. The precise spatial and temporal properties of these “retinal waves” have been implicated in the formation of retinal projections to the brain. However their role in the development of direction selective circuits within the retina has not yet been determined. We addressed this issue by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…We cannot discount the possibility that developmental compensation has occurred at sites not examined in this study. However, our findings are consistent with multiple previous studies that demonstrate that the early development of retinal direction selectivity is highly resistant to changes in neural activity (Chan and Chiao, 2008; Elstrott et al, 2008; Hamby et al, 2015; Sun et al, 2011; Wei et al, 2011). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We cannot discount the possibility that developmental compensation has occurred at sites not examined in this study. However, our findings are consistent with multiple previous studies that demonstrate that the early development of retinal direction selectivity is highly resistant to changes in neural activity (Chan and Chiao, 2008; Elstrott et al, 2008; Hamby et al, 2015; Sun et al, 2011; Wei et al, 2011). …”
Section: Discussionsupporting
confidence: 93%
“…Although multiple studies have demonstrated that the emergence of retinal direction selectivity occurs independent of neural activity (Elstrott et al, 2008; Hamby et al, 2015; Sun et al, 2011; Wei et al, 2011), we needed to rule out potential developmental changes in this circuit in Gabra2 KO mice. Therefore, we examined other critical synapses involved in direction selectivity: the GABAergic and cholinergic synapses between SACs and DSGCs.…”
Section: Resultsmentioning
confidence: 99%
“…We observed a reduction in eye-specific segregation induced by dark-rearing prior to eye-opening (Figure 4). The magnitude of this reduction is comparable to several other manipulations that disrupt eye-specific segregation (Kirkby et al, 2013), including interference with the complement cascade [for example, see (Bialas and Stevens, 2013)], targeted killing of ipRGCs (Chew et al, 2017), and disruption of glutamatergic waves (Blankenship et al, 2011; Hamby et al, 2015; Xu et al, 2010). Interestingly, we found that retinal projections to non-image-forming parts of the brain—the vLGN and OPN—undergo developmental eye-specific refinement, but not in a light-dependent manner (Figure S3).…”
Section: Discussionmentioning
confidence: 55%
“…CaV3.2 knockout mice exhibit disrupted waves during the period that direction selective circuits are established, from P11–P14, however, after eye-opening their direction selective ganglion cells (DSGCs) are indistinguishable from wild type mice 18 . Development of the retina’s direction selective circuits depends on an asymmetry in synapse number between inhibitory starburst amacrine cells (SACs) and DSGCs 19 , a circuit that emerges in an activity-independent manner 20 .…”
Section: Retinamentioning
confidence: 99%